Using RFID for tracing cumulated resources and emissions in supply chain. (11th November 2011) - Junkkari, Marko; Sirkka, Antti
The tracing of resources and emissions has been recognised increasingly important in supply chains. The developed traceability graph enables tracing of information associated with products and their parts. Tracing in a supply chain requires the three integrated levels of actions: 1 at the physical level the Radio-Frequency Identification (RFID) is used for physical objects; 2 at the data-storing level logical counterparts of RFID tags and database objects are mapped; 3 operational actions determine how recourses, emissions etc. are portioned in different parts of the traceability graph. Briefly, we integrate RFID technology with databases and operational actions of the supply chain.